1989
DOI: 10.1002/macp.1989.021900703
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of poly(α‐malic acid) and its hydrolysis behavior in vitro

Abstract: Biodegradable poly(a-malic acid) (7) was synthesized by means of ring-opening homopolymerization of malide dibenzyl ester (9, which is a cyclic dimer of b-benzyl malate. In order to obtain a high-molecular-weight biodegradable lactic acid type polyester having pendent modifiable groups, ring-opening copolymerization of malide dibenzyl ester with L-dilactide was applied to give poly(a-malic acid-co-lactic acid) (10). It was found from the results of hydrolysis of poly(a-malic acid) that the main-chain ester bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 14 publications
2
89
0
1
Order By: Relevance
“…[3,4,6,7] Examples of functional cyclic diesters and related polyesters are reported in Table 2. Poly(a-malic acid) (1c), which can be regarded as a functional analog of poly(lactic acid), has been prepared by Ouchi and Fujino [15] by ROP of malide dibenzyl ester (1a), a cyclic dimer of b-benzyl malate, followed by debenzylation. Similarly, Kimura et al [16,17] His laboratory (40 people) is concerned with the macromolecular engineering of synthetic polymers based on living/controlled anionic, radical and ring-opening polymerization.…”
Section: Polyesters From Cyclic Diestersmentioning
confidence: 99%
“…[3,4,6,7] Examples of functional cyclic diesters and related polyesters are reported in Table 2. Poly(a-malic acid) (1c), which can be regarded as a functional analog of poly(lactic acid), has been prepared by Ouchi and Fujino [15] by ROP of malide dibenzyl ester (1a), a cyclic dimer of b-benzyl malate, followed by debenzylation. Similarly, Kimura et al [16,17] His laboratory (40 people) is concerned with the macromolecular engineering of synthetic polymers based on living/controlled anionic, radical and ring-opening polymerization.…”
Section: Polyesters From Cyclic Diestersmentioning
confidence: 99%
“…The initial pH values of the nanospheres suspensions were 6.1, 4.5 and 3.6 for the PMLABeloo, PMLABe9oHlo and PMLABesoH2o, respectively, as measured employing a Micro protein resistant combination electrode (Whatman, Maidstone, UK) connected to a pH meter (Coming, Halstead Essex, UK). The pH of the degradation medium was not adjusted to the same value for all the systems since it has been reported that, although strong acidic and alkaline media dramatically affect polyester degradation, pH values in the range 4 to 6 do not have a significant effect on degradation [16,17]. Sodium azide (0.02% w/v) was added as a preservative.…”
Section: Degradation Study Proceduresmentioning
confidence: 99%
“…PMA is synthesized in two ways. Many researchers have synthesized the poly-a-malic acid ester or poly-h-malic acid ester through ring-opening polymerization [7,[12][13][14][15][16]. This synthesis is difficult, however, because of the number of steps involved in the reaction cycle, including repeated purification, although these methods yield high molecular weight (HMW) polyesters.…”
Section: Introductionmentioning
confidence: 99%